Implementation of the JUMPAJA Program Based on Local Wisdom in Strengthening the Pancasila Student Profile in Elementary Schools - Anisa Diyah Rahmah; Novia Rahma Rista Utami; Uci Ulfa Nur’afifah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study analyzes the implementation of the JUMPAJA (Javanese Market Friday) Program, a local wisdom-based school culture innovation developed by SDN Tambakromo 2, Ngawi Regency, which utilizes the Javanese market calendar cycle as a framework for integrating cultural values into weekly habituation activities aimed at strengthening the Pancasila Student Profile through systematic planning, implementation, and evaluation processes in elementary education. This research employed a qualitative approach with a case study design. Data were collected through non-participant observation, semi-structured interviews, and documentation involving the principal, teachers, and students, then analysed using the interactive model of Miles and Huberman through data condensation, data display, and conclusion drawing. The findings indicate that the program was collaboratively planned and systematically implemented through five habituation activities, namely Jumat Kliwon (Cultural Friday), Jumat Legi (Play Friday), Jumat Pahing (Sharing Friday), Jumat Pon (Clean Friday), and Jumat Wage (Worship Friday). The findings indicate that the JUMPAJA Program successfully strengthened several dimensions of the Pancasila Student Profile, particularly faith and devotion to God Almighty and noble character (beriman dan bertakwa kepada Tuhan Yang Maha Esa serta berakhlak mulia) through religious habituation activities, mutual cooperation (gotong royong) through collaborative participation in cultural and social activities, creativity (kreatif) through students’ involvement in traditional cultural performances and entrepreneurial practices, and global diversity (berkebinekaan global) through the appreciation, preservation, and understanding of Javanese cultural values as part of national identity. Continuous evaluation and reflective coordination meetings also supported the program's sustainability and ongoing improvement. This study concludes that local wisdom-based school culture can function as an effective pedagogical strategy for strengthening the dimensions of the Pancasila Student Profile and contributing to contextual character education practices in elementary schools.